Ta’tsiir Thoriiqah Murabba’ al-Kalimaat fii Tarqiyyah Mufrodaat al-Lughah al-Arabiyyah lada Thullaab al-Shaff al-Tsaamin bi Madrasah Salafiyyah al-Rahmah al-Mutawashithah al-Islaamiyyah Bonder li al-Sanah al-Diraasiyyah 2020-2021 - Baiq Laili Rahmawati; Baiq Rozalina Deswari; Wirawan Jamhuri (UIN Maulana Malik Ibrahim Malang, 2023)
This research departs from the need for good Arabic language learning with good methods. One method that can be used is the word square method which provides opportunities for students to build their knowledge more actively and creatively, especially in mufrodat learning. This research is research that uses a quantitative approach with a pre-experimental type, namely the pretest-posttest design which aims to determine the effect and extent of the influence of the word square method in improving the Arabic mufradat of class VIII students at MTs Ar-Rohmah Bonder, Central Lombok, NTB. Data collection techniques in research using questionnaires and tests then the results of the two instruments were analyzed using the t-test with the help of SPSS, while the steps taken in data analysis were: validity, reliability, questionnaire data analysis, hypothesis testing, analysis of learning outcomes hypothesis testing. Based on the results of data analysis, the researcher found that there was an effect of the word square method in increasing the mufradat of class VIII students of MTs Ar-Rahmah Bonder, Central Lombok, NTB, which indicated that there had been an increase in the average student learning score from 46.00 to 79.60. It is shown in the related table for the sample t that the value of sig. (2-tail) In the data obtained learning outcomes of 0.000, which is less than 0.05, it can be concluded that the hypothesis Ha from research related to learning outcomes can be accepted and H0 is rejected.